2020
DOI: 10.4081/or.2020.8399
|View full text |Cite
|
Sign up to set email alerts
|

Are physical therapy pain levels affected by surgical approach in total hip arthroplasty? A randomized controlled trial

Abstract: The main objective of this study was to evaluate the difference in pain levels during postoperative physical therapy pathways in patients who underwent a cement less total hip replacement either through a muscle sparing direct anterior approach (DAA), or the classic trans-gluteal lateral approach (LA). One hundred and twelve (112) patients were randomized into two equal groups. Baseline values of myoglobin levels were acquired prior to surgery and repeated at 6 hours postoperatively as a biomarker for muscle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hence, muscle splitting is avoided and soft tissue injury is minimised [8,43]. This is supported by biochemical and radiological evidence, with reports of lower levels of early post-operative creatine kinase or myoglobin, which are indicators of muscle damage, in DAA compared to other approaches [28,34,38,39]. Post-operative MRI studies also noted less muscle and tendon damage in DAA than LA [34].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Hence, muscle splitting is avoided and soft tissue injury is minimised [8,43]. This is supported by biochemical and radiological evidence, with reports of lower levels of early post-operative creatine kinase or myoglobin, which are indicators of muscle damage, in DAA compared to other approaches [28,34,38,39]. Post-operative MRI studies also noted less muscle and tendon damage in DAA than LA [34].…”
Section: Discussionmentioning
confidence: 86%
“…Overall, 14 of 24 RCTs involved surgeons experienced in DAA, [ 19 22 , 24 27 , 29 , 30 , 32 , 35 , 40 , 42 ]. The remainder either involved surgeons still within the learning curve [ 28 , 31 , 33 , 36 38 , 41 ] or did not specify surgeon experience [ 23 , 34 , 39 ]. Complication risks during the learning curve of DAA can potentially be reduced with adequate supervision and guidance by experienced surgeons and by performing initial cases on less complex patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were from USA, Europe and China. The numbers of included studies were thirteen PA vs DAA[ 53 , 54 , 56 - 58 , 69 , 75 , 84 , 85 , 87 , 88 , 94 , 96 ], thirteen LA vs DAA[ 55 , 59 , 61 , 67 , 71 , 74 , 76 , 77 , 79 , 81 , 82 , 86 , 97 ], seven PA vs LA[ 63 , 65 , 83 , 90 - 92 , 95 ], one PA vs two-incision[ 60 ], one PA vs LA vs two-incision[ 72 ], three LMIS vs LA[ 66 , 70 , 80 ], seven DSA/SuperPath vs PA[ 18 , 19 , 64 , 68 , 73 , 78 , 93 ] and two DSA/SuperPath vs LA[ 62 , 89 ]. The mean age was 51 to 76 years, BMI 21-31 kg/m 2 , 13%-65% male and 20%-100% had hip osteoarthritis (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Copay affordability, scheduling outpatient appointments, and arranging transportation have been demonstrated to be legitimate barriers to accessibility to outpatient PT for THA patients after discharge [ 10 , 11 ]. PT exercises can also be painful, as one of the most commonly asked questions regarding PT in the postoperative period after THA is about pain expectations [ 26 ]. Additionally, Yayac et al demonstrated that TJA patients who underwent supervised PT had a significantly higher readmission rate than those who were discharged with self-directed home exercise regimens [ 9 ].…”
Section: Reviewmentioning
confidence: 99%